Assessment of accountability practices in the public sector in Malaysia / Jamaliah Said, Md. Mahmudul Alam and Razana Juhaida Johari. - Said, Jamaliah; Alam, Md. Mahmudul; Johari, Razana Juhaida (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2018)
Ensuring accountability in the public sector is a very crucial issue as it could lead to failures in governance, fraud, inefficacy, corruption as well as weak financial management. This study evaluated the state of the present accountability practices among public sector employees from various Malaysian service schemes. Primary data were collected, using a questionnaire survey approach with 194 heads of departments in the Malaysian federal ministries. Data was collected in accordance with the perspective of 12 factors in accountability practices, using a five-point Likert scale. Factor analysis and descriptive statistics were utilized for data analysis. In addition, data reliability was checked by the Cronbach's alpha test; data normality was examined by the Skewness and Kurtosis tests, and data validity was tested by using the Kaiser-Meyer Olkin test and Barlett's test. The findings show that 94.9% of the participants reported that they practised accountability within their departments. Nevertheless, the priority for these accountability factors varied according to the service schemes. In general, the perceived accountability practice was the highest within the group in the administrative scheme and the lowest among the employees under the accounting scheme. Moreover, the perceived accountability practice of the audit scheme was below the general average level. These findings would help policy makers to take necessary steps to improve the practices of accountability for creating a more dependable and efficient public sector in Malaysia.